IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM PEMBERDAYAAN GURU PADA SMP NEGERI 6 KOTA BANDA ACEH - Arslan .; Murniati AR AR; Djailani . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: School based management is a management which gives the bigger authority on the school in making and implementing the policies in empowering the teachers. The empowering teachers’ purpose is to improve the teachers’ ability in developing the quality’s learning. This research intends to get the data of the SBM implementation in empowering the Junior high school teachers in Banda Aceh by using descriptive, qualitative research’s method on the headmaster, vice of the headmaster and teachers as the subjects of the research. The techniques in collecting the observation’s data are interview, study of documentation and qualitative data analysis, this research summarizes that (1) the headmaster has already arranged the SBM program in empowering teachers comprehensively. (2) The implementation in empowering the teachers has already been done based on the intended purposes and (3) the obstacles which are faced in implementing SBM in empowering the teachers is the situation and the way of the teachers’ work still poorly in general.Keywords: The school based management in empowering the teachers.Abstrak: Manajemen berbasis sekolah adalah pada manajemen yang memberikan kewenangan yang lebih besar kepada sekolah untuk membuat dan melaksanakan kebijakan-kebijakan dalam pemberdayaan guru. Pemberdayaan guru bertujuan menambah kemampuan dan keterlibatan guru dalam membuat program mengembangkan pembelajaran berkualitas. Penelitian ini bertujuan untuk mendapatkan data tentang implementasi Manajemen Berbasis Sekolah dalam pemberdayaan guru SMPN 6 kota Banda Aceh dengan mempergunakan metode penelitian diskriptif kualitatif subjek penelitian kepala sekolah, wakil kepala sekolah dan guru, teknik pengumpulan observasi, wawancara, studi dokumentasi dan analisis data secara kualitatif, peneliti memberi kesimpulan. 1)Kepala sekolah telah menyusun program MBS memperdayakan guru yang koperensif 2)Pelaksanaan pemberdayaan guru dilaksanakan sesuai dengan tujuan yang ingin dicapai dan 3) hambatan yang dihadapkan dalam penerapan MBS dalam pemberdayaan guru adalah situasi da cara kerja umumnya masih rendah.Kata Kunci: Manajemen Berbasis Sekolah untuk Pemberdayaan Guru